2009
DOI: 10.1159/000211666
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Osteoprotegerin and sRANKL Concentrations in the Perinatal Period at Term

Abstract: Background: Intrauterine growth restriction (IUGR) has been associated with low bone mass in infancy and increased risk for osteoporosis development in adult life. Osteoprotegerin (OPG) and receptor activator of nuclear factor-κB ligand (RANKL) are main determinants of bone resorption. Objectives: To investigate OPG and soluble RANKL (sRANKL) concentrations in maternal, fetal and neonatal serum of IUGR patients and appropriate for gestational age (AGA) pregnancies. Additionally, plasma intact parathormone (PTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In agreement to our data, Naylor et al obtained low OPG levels in neonates and suggested its placental origin (23), a concept supported by the marked decrease of OPG in maternal blood after delivery. Likewise, low OPG in neonatal serum was observed by Brianna et al and the authors concluded that it could represent high bone resorption rates (40). Indeed, in our study, an inverse correlation was noticed between umbilical serum OPG and umbilical serum BAP, a marker of bone turnover.…”
Section: Discussionsupporting
confidence: 79%
“…In agreement to our data, Naylor et al obtained low OPG levels in neonates and suggested its placental origin (23), a concept supported by the marked decrease of OPG in maternal blood after delivery. Likewise, low OPG in neonatal serum was observed by Brianna et al and the authors concluded that it could represent high bone resorption rates (40). Indeed, in our study, an inverse correlation was noticed between umbilical serum OPG and umbilical serum BAP, a marker of bone turnover.…”
Section: Discussionsupporting
confidence: 79%
“…Neither the observed relationships nor infant characteristics were significantly influenced by maternal or infant race. A study by Briana et al found no significant association between cord OPG concentrations and birth weight, and no difference in OPG between appropriate-for-gestational-age (n 5 20) and intrauterine growth restriction (n 5 20) infants; 23 however, their relatively small sample size may have limited their ability to detect associations. Our observed association between cord OPG concentrations and neonatal birth weight z-score may hint at a role for OPG in neonatal accrual of body stores of fat, bone or muscle.…”
Section: Discussionmentioning
confidence: 95%
“…The rapid post partum fall in OPG suggests a placental origin, which has been corroborated by the finding of a high concentration of OPG in placental membranes (40). The circulating levels of RANKL have been investigated in studies that have reported parallel changes to those of OPG (41,42). However, these data require a cautious interpretation because of the methodological problems with current assays for measurement of serum RANKL.…”
Section: Other Regulatorsmentioning
confidence: 96%